A step backwards in Serbia - Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2004)
The candidate with the best chances to win the first round of the Serbian presidential election on June 13 is the 52-year old construction engineer, Tomislav Nikoli , a member of the ultra-nationalist populist Serbian Radical Party (SRS). Despite the expected devastating domestic and international consequences of a Nikoli victory, Serbia (SWP Comments / SWP)
Keywords: 320